Emergency Reporting System via Smartphone the Case Study of the Rajamangala University of Technology Thanyaburi (RMUTT) - Janratchakool, Weena; Yoosooka, Burasakorn; Chomchaiya, Suvil; Sukjai, Napasorn; Thabured, Thanida (Progress in Applied Science and Technology, 2024)
The major objective of this research project is to develop a smartphone-based emergency reporting system, the case study of the Rajamangala University of Technology Thanyaburi (RMUTT). This was about to be the preliminary source for first aid instructions for major system users: students and paramedic staff (ambulance drivers and medical attendants). RMUTT’s students, faculties, and staff can not only report in case of any accidents or emergencies but also follow the system-provided first aid instructions. Paramedic staff can be reported to and can reply to the reporters. The development tools for websites and mobile applications are the Visual Studio Code with MySQL and phpMyAdmin as database engine. The overall 16 system functional features were tested for accuracy, and all were 100% accurate, which means that the system was comprehensively developed where all system objectives were satisfied. The expert evaluation result was a GOOD level ( = 4.43) where the 0.48 in standard deviation (S.D. = 0.48) means no significance. System evaluation by major users (paramedic personnel) is in GOOD level ( = 4.24) where the where the 0.71 in standard deviation (S.D. = 0.71) implied the significance.